The dimensionality of the Portuguese party policy space - Camões, Pedro J. (2002)
We provide a comprehensive analysis of the Portuguese parties and their policy space. We show how and how well the parties have been able to adapt to the changing environment in the party system. Our analyses show that, not only are we able check existing static expert assessments of the Portuguese party and policy space, but we are also able to track the dynamics of the system. In this way, we expand on what little has been said thus far about the Portuguese party system. We conclude with three important ideas. First, we confirm that the Portuguese policy space is unidimensional, with the parties lining up from Left to Right, as some but not all experts, have suggested. Second, we propose that the environment of the Portuguese party system is one of compression, that is, parties have been office-seekers in that they have all been approaching the Centre of the political spectrum for a number of reasons we explore in detail. Last, we learn that only through issue dimensions and how parties pronounce themselves on these dimensions are the smaller parties able to survive and avoid extinction in the compressing environment of the party system. *Mendes and Camões are grateful to the University of Minho. And all of us wish to thank Ian Budge and Andrea Volkens for providing us with updated data of the manifestoes.